Environmental effects of consumption: An approach using DEA and cost sharing - Hans Keiding (Fondazione Eni Enrico Mattei (FEEM), 2002)
In the paper we propose an to evaluation of the environmental effects of consumption activities. The approach consists of two steps, namely (1) assignment of environmental effects to consumption activities, for which we propose to use the methods of (multidimensional) cost sharing, and (2) a comparison of the effects of different consumption activities using Data Envelopment Analysis (DEA), in which relative indices of pollution for the actitivies can be computed.An application is given using Danish national account data.
Keywords: D24; C71; Q25; 330; consumption activities; environmental effects; cost sharing; data envelopment analysis; Konsumgut; Umweltbelastung; Data-Envelopment-Analyse; Externer Effekt; Kostenfunktion; Theorie